Paradise regained: older adult rock climbers turning space into place in the natural environment - Mark Hickman; Colin Beard; Alison Inkster (Envigogika, 2015)
At the time of writing there are over 10 million people aged over 65 living in the UK, and by 2050 the number is predicted to rise to 19 million. This expansion of the ageing population is mirrored worldwide, and over the past ten years has stimulated a growth in age-related studies. However, the idea of a social gerontology of the outdoors is yet to take root. Yet, with the maturing of those born between the years 1946 and 1964, and increased participation in adventurous activities, we suggest that the time is right for scholarship in this specific direction. Accordingly, the aim of this study was to discover how older adult rock climbers perceived their relationship with the natural environment to have changed over the period of their involvement with rock climbing. The investigation used a purposive sample of rock climbers in the north-west of England (n=10) aged between 65 and 74 years (av=69.6) identifying them as ‘young-old’ adults. Oral testimony was collected over two phases, the first with interview-questionnaires, and the second with targeted semi-structured interviews. In order to give a clear voice to participants, manual data handling using was used to establish raw data that were then sorted into themes and verified against internal and external checkers. These were then organized around Peace, Wahl, Mollenkopf and Oswald’s (2014) concept of an ‘environment’ considered within three dimensions: the physical/material, including the natural landscape; the psychological, and the meaning attributed to the place, its evolution across the life course, and how it makes people feel about themselves; and the social/cultural, involving the engagement of people to places, including how the space is used and remembered.